Design of a Battery-less Micro-scale RF Energy Harvester for Medical Devices - Pirapaharan, K.; Gunathillake, W.L.A.D.A.; Lokunarangoda, G.I.; Nissansani, M.V.; Palihena, H.C.; Hoole, P.R.P.; Aravind, C.V.; Hoole, S.R.H. (International Conference on Biomedical Engineering and Sciences, 2012)
This paper presents a micro-scale RF (radio frequency) energy harvesting circuit that can be used for RF signals for milliwatt to microwatt scale DC power units. Both at hospitals and homes, radio waves are always present in our daily lives in the form of signals transmitted from TV, Radio and Mobile base stations. There are many signals of different frequencies in our surroundings that can be reclaimed via a harvester. Even though these signals carry a small amount of energy, the possibility of using that to energize devices is promising. The methodology of this work is to analyze the RF energy spectrum to identify the most available RF energy sources. Based on that we design an appropriate antenna to capture that spectral power and replicate a circuit that can convert micro-scale RF energy received via the antenna into usable electrical power. Finally, the harvester circuit is used to feed power to a table clock and successfully demonstrated. The limitations are noted along with how the system may be improved through better antenna design. This harvester design is unique in not using a battery
Keywords: RF energy harvesting; Micro scale energy harvesting; Voltage multiplier circuit